Formulation of Mosquito Repellant Freshener Gel with China Grass as Gel Base and Lemon Grass Oil as Mosquito -Repellant - Reddy, Bhargava; B, Sambasiva Reddy; K, Mahesh; R, Hari Prasad Reddy; Tony, D. Eswar; Nadendla, Rama Rao (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: Mosquitoes transmit severe diseases, including malaria, dengue, and Zika virus, necessitating effective mosquito repellents. While traditional repellents are typically sprays or lotions, these can be inconvenient and leave residues. A more convenient alternative is mosquito repellent gel, offering ease of application, lasting effects, and a more enjoyable user experience. This study focuses on a gel-based mosquito-repelling air freshener containing lemongrass oil, known for its mosquito-repelling properties and fresh citrus-like scent. Methodology: The study developed a mosquito repellent gel infused with lemongrass oil, containing active constituents such as neral, isoneral, and limonene. Sensory assessments evaluated the gel’s color and odor using 150 individual’s comments, and a hedonic test was conducted with 180 participants aged between 25-30 to assess product acceptability when applied to clothing and inanimate objects. To determine the longevity of the gel, total liquid evaporation was measured by weight loss over a four-week period, and the repellent's effectiveness was tested in a closed room. Results: Sensory assessment confirmed an acceptable color and a citrus-like odor for the gel, while the hedonic test indicated a favorable user response. Weight loss calculations demonstrated the gel's sustained presence over time. The closed-room test confirmed the gel's effectiveness in repelling mosquitoes. Conclusion: The lemongrass oil-based mosquito repellent gel is a promising alternative to traditional repellents, offering both user convenience and effective mosquito protection. Its long-lasting formula and positive sensory characteristics make it a viable option for personal and environmental use in mosquito-prone areas.